The prayer life of Jesus shout of agony, revelation of hope : a commentary - Spencer, William David, 1947-; Spencer, Aida Besancon (Lanham, MD University Press Of America, 1990)
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- prayers; Bible. N.T. Gospels -- criticism, interpretation, etc